2010
DOI: 10.1002/hfm.20220
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial risk exposures and musculoskeletal disorders across working‐age males and females

Abstract: In 2008, The European Agency for Safety and Health at Work (EU-OSHA) reported that musculoskeletal disorders (MSDs) were the most common work-related health problem in Europe. Females are considered more susceptible to MSDs than are males, and older workers are more vulnerable than are younger workers. Factors specific to the job, work organization, and individual have been implicated as potential risk factors, with current interest focusing on psychosocial risk factors and the pathology of disorders. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 42 publications
(51 reference statements)
1
31
0
Order By: Relevance
“…First of all, aging affects the physical faculties such as strength, vision, and reaction times (Wiker, Schwerha, & Jaraiedi, 2009). Aging also causes a number of pathologies (Collins & O'Sullivan, 2010), which often require medical treatment. An individual suffering from deterioration of his or her physical condition walking on slippery or contaminated surfaces is more likely to slip and fall.…”
Section: Introductionmentioning
confidence: 99%
“…First of all, aging affects the physical faculties such as strength, vision, and reaction times (Wiker, Schwerha, & Jaraiedi, 2009). Aging also causes a number of pathologies (Collins & O'Sullivan, 2010), which often require medical treatment. An individual suffering from deterioration of his or her physical condition walking on slippery or contaminated surfaces is more likely to slip and fall.…”
Section: Introductionmentioning
confidence: 99%
“…As Collins & O'Sullivan published in , although the European Agency for Safety and Health at Work reported that women and older workers were more susceptible to musculoskeletal disorders, we found disagreements in the literature consulted on a causal relationship between these types of disorders and the variables, gender and age (Collins & O'Sullivan, ; García Gómez, Castañeda López, Herrador Ortiz, & Simon Soria, ).…”
Section: Discussionmentioning
confidence: 65%
“…Das and Mabaleka (2009) investigated the effects on the muscles by electromyographic study during asymmetric lift of load from the floor. Psychosocial risk exposures and MSDs across working‐age men and women were investigated by Collins and O'Sullivan (2010). Tetteh, Latif, McGlothlin, & Peters (2009) investigated the impacts of lift frequency and posture on body mass index.…”
Section: Literature Reviewmentioning
confidence: 99%